A Handbook for Scholars Revised Edition - Leunen, Mary Claire van (New York Oxford University Press, 1992)
A complete guide to the mechanics of scholarly writing: citation, references, footnotes, bibliographies, format, styling, text preparation, and related matters.
Keywords: Academic writing -- Handbooks, manuals, etc. Authorship -- Handbooks, manuals, etc. Scholarly publishing -- Handbooks, manuals, etc